Война диверсантов - Зверев Сергей Иванович (Журнал боевых действий. Сильные романы, 2018)
Экземпляры: ф.11 (20180801) / Инвентарный номер: 55692 / Цена: 109.00 / Авт.знак: З-43 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6